Upaya Penanggulangan Tindak Pidana Pelecehan Seksual dalam Kasus Gilang “Bungkus” - Andika Tri Wibowo; Laras Astuti (Universitas Muhammadiyah Yogyakarta, 2024)
Sexual harassment is a complex problem, and the phenomenon of fetishes has become part of the dynamics of sexual harassment that is widespread. Victims of sexual harassment experience various impacts, which are made even more difficult by the reluctance of victims to report sexual harassment. The Gilang Bungkus case is one of the cases that has attracted attention because sexual harassment occurred on campus with several academics becoming victims. This research aims to explore the understanding of the dynamics of sexual harassment by focusing on mitigation efforts through the judge's decision in the Gilang Bungkus case. Normative research methods are used in this research by focusing on legal rules or regulations through document studies of secondary data and to complete and validate secondary data, this is also done through interviews with sources. Based on the research results, it can be concluded that efforts to overcome criminal acts of harassment in the Gilang Bungkus case were carried out through penal and non-penal measures. Penal efforts focus on imposing prison sentences based on the number of victims, as well as the impact of losses through the role of Judges and the Police, while non-penal efforts are carried out through various preventive measures involving youth leaders, religious leaders, community leaders and educational leaders.